Study on fragmentation characteristics of rock mass in bench blasting with different coupling media - Li, Tong; Chen, Ming; Guo, Bo-wen; Song, Li; Fan, Bing; Cui, Shan-shan (Frontiers in Earth Science, 2024)
The fragmentation size distribution is an important index to evaluate blasting effect. Based on stress wave theory, a blasting fragmentation distribution model is established, and the key influencing factors were clarified. Then, the distribution characteristics of rock fragmentation in water-coupled blasting and air-coupled blasting were compared and verified by numerical simulation and field test. The results show that the rock blasting fragmentation size is negatively correlated with borehole pressure and unit explosive consumption when blasting rock is determined. The existence of water slows down the attenuation of blasting load, prolongs the duration, and makes the blasting pressure transmitted to hole wall significantly greater than air-coupled one, which is equivalent to increasing the unit explosive consumption.Moreover, the rock fracture development speed and fragmentation degree of water-coupled blasting is significantly higher than air-coupled blasting. Comprehensively determined in same charging parameters, water-coupled blasting compared with air-coupled blasting can improve the degree of rock fragmentation, the average size of rock after blasting is smaller, more uniform particle size distribution. The research results for the control of blasting and optimization of explosive energy utilization have important reference significance.